Pengaruh Literasi Keuangan dan Perilaku Keuangan terhadap Keputusan Investasi Mahasiswa - Upadana, I Wayan Yasa Adi; Herawati, Nyoman Trisna (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
The purpose of this study is to find out and measure how the influence of Financial Literacy and Financial Behavior on Student Investment Decisions and also the differences in investment decisions between students of Udayana University and Ganesha Education University. This research is quantitative or related to numbers as a benchmark. Data were collected using a questionnaire or questionnaire using random sampling techniques distributed to 200 respondents or students. In this study, researchers used descriptive data analysis techniques, regression tests and t-test different tests with the help of SPSS software program version 24. The results of this study indicate that financial literacy has a positive effect on investment decisions. Financial behavior has a positive effect on investment decisions. The results of this study also showed that there were no differences in student investment decisions